Contributing factors and quality of life among women with abnormal uterine bleeding - Behera, Subhasmita; Gomathi, B.; Behera, Kshyanaprava (International Journal of Research in Medical Sciences, 2022)
Background: Abnormal uterine bleeding (AUB) is one of the most common debilitating menstrual problems and it has a major impact on quality of life. Methods: A explorative research design was adopted to study the contributing factor and quality of life. Hundred and fifty (150) women with AUB were selected purposively from gynecology OPD of IMS and SUM Hospital, Bhubaneswar, Odisha. The tools used for the study were 1) the socio-demographic questionnaire, 2) questionnaire to assess the contributing factors and 3) WHOQOL-BREF questionnaire to assess the quality of life. The data were analyzed using descriptive and inferential statistics. Results: Highest percentage of women (46.66%) were aged between 46 and 50. Majority of women had mental stress (72.67%) and were non-vegetarian (66%). Half of the (50.66%) women had a family history of AUB, and 16.66% of women had a family history of malignancy. Majority (76.66%) of women were diagnosed with medical conditions and among the highest percentage (27.84%) of them had thyroid diseases. The overall quality of life score was 65.08±11.19 and the social relationship domain (38.72±7.11) was more affected and the environmental domain (75.94±4.12) was least affected. Conclusions: Various factors are involved in the development of abnormal uterine bleeding. There is a need for awareness about the contributing factors and prevention of AUB among reproductive-age women.